Overexpression of 18S rRNA methyltransferase CrBUD23 enhances biomass and lutein content in Chlamydomonas reinhardtii - Liu, Chenglong; Guo, Haoze; Zhao, Xinmei; Zou, Bingxi; Sun, Ting; Feng, Jinwei; Zeng, Zhiyong; Wen, Xueer; Chen, Jun; Hu, Zhangli; Lou, Sulin; Li, Hui (Frontiers in Bioengineering and Biotechnology, 2023)
Post-transcriptional modification of nucleic acids including transfer RNA (tRNA), ribosomal RNA (rRNA) and messenger RNA (mRNA) is vital for fine-tunning of mRNA translation. Methylation is one of the most widespread post-transcriptional modifications in both eukaryotes and prokaryotes. HsWBSCR22 and ScBUD23 encodes a 18S rRNA methyltransferase that positively regulates cell growth by mediating ribosome maturation in human and yeast, respectively. However, presence and function of 18S rRNA methyltransferase in green algae are still elusive. Here, through bioinformatic analysis, we identified CrBUD23 as the human WBSCR22 homolog in genome of the green algae model organism Chlamydonomas reinhardtii. CrBUD23 was a conserved putative 18S rRNA methyltransferase widely exited in algae, plants, insects and mammalians. Transcription of CrBUD23 was up-regulated by high light and down-regulated by low light, indicating its role in photosynthesis and energy metabolism. To characterize its biological function, coding sequence of CrBUD23 fused with a green fluorescence protein (GFP) tag was derived by 35S promoter and stably integrated into Chlamydomonas genome by glass bead-mediated transformation. Compared to C. reinhardtii wild type CC5325, transgenic strains overexpressing CrBUD23 resulted in accelerated cell growth, thereby leading to elevated biomass, dry weight and protein content. Moreover, overexpression of CrBUD23 increased content of photosynthetic pigments but not elicit the activation of antioxidative enzymes, suggesting CrBUD23 favors growth and proliferation in the trade-off with stress responses. Bioinformatic analysis revealed the G1177 was the putative methylation site in 18S rRNA of C. reinhardtii CC-849. G1177 was conserved in other Chlamydonomas isolates, indicating the conserved methyltransferase activity of BUD23 proteins. In addition, CrTrm122, the homolog of BUD23 interactor Trm112, was found involved in responses to high light as same as CrBUD23. Taken together, our study revealed that cell growth, protein content and lutein accumulation of Chlamydomonas were positively regulated by the 18S rRNA methyltransferase CrBUD23, which could serve as a promising candidate for microalgae genetic engineering.